The transition from pediatric to adult rheumatology care through creating positive and productive patient-provider relationships: an opportunity often forgotten - Semalulu Teresa; McColl Jeanine; Alam Arzoo; Thomas Steffy; Herrington Julie; Gorter Jan Willem; Cellucci Tania; Garner Stephanie; Heale Liane; Matsos Mark; Beattie Karen A.; Batthish Michelle (De Gruyter, 2021)
The transition of patients with a chronic rheumatic disease from pediatric to adult care has been characterized by poor medical and patient-centered outcomes due to the lack of comprehensive transition programs and the paucity of evidence to guide practitioners. We describe a multidisciplinary transition program, data assessing patients' preparedness for transition and perception of care providers, and the association between these outcomes.